UJI BEDA PENGARUH GENDER TERHADAP MARKETING COMMUNICATION OF POLITICAL PARTY PADA 5 PARTAI PEMENANG PEMILIHAN UMUM LEGISLATIF TAHUN 2014 DI KOTA PONTIANAK - admin, ATIKA MULANSARI B1021131111 (Jurnal Manajemen Update, 2017)
This reseacrh aims to determine the influence of Marketing Communications consisting of Advertising, Personal Sales, Sales Promotion, Public Relations, and Direct Marketing can encourage selected decisions by male and female voters against legislative parties in 2014 in Pontianak (PDI Perjuangan , NASDEM, GOLKAR, PAN and PKB). This research consists of the independent variables of advertising, personal selling, sales promotion, public relations, and direct marketing and the dependent variable is the decision to vote. Type of explanatory research with quantitative approach, while the data data technique using questionnaires with some respondents. The population in this study were voters in the city of Pontianak, with a total sample of 120 respondents. Sampling using purposive sampling technique with analytical tool used is descriptive analysis. The results of this research Advertising, Personal Sales, Sales Promotions, Public Relations and Direct Marketing. Positive above the elected decision in the elected party in 2014 in Pontianak City (PDI Perjuangan, NASDEM, GOLKAR, PAN and PKB). Advertising, Sales Promotion, Personal Sales, and Direct Marketing of Decisions Choosing There is a Difference Between Men and Women. All variables indicate that female women have a higher value. Variable Public Relations that show the voter has a higher value.